ILLEGAL ORGAN TRANSPLANTATION AS A MODUS OPERANDI OF TRAFFICKING IN PERSONS: A LEGAL AND HUMAN RIGHTS ANALYSIS OF VICTIM PROTECTION - Susanti, Heni; Yanti, Evi (Proceeding International Conference on Social Sciences, 2026)
This study aims to first analyze the juridical construction of illegal organ transplantation as a modus operandi of human trafficking in the Indonesian positive legal system; and second, to examine the form and effectiveness of legal protection for victims of illegal organ transplantation within the framework of health law and the Law on the Eradication of Trafficking in Persons. The method used in this paper is a normative juridical method, with a legislative approach. The results of this study are that the construction of criminal law regulations against illegal organ transplantation in Indonesia has not been built as a complete and independent legal regime, but is spread across various sectoral laws and regulations and the effectiveness of legal protection for victims of illegal organ transplantation in Indonesia is still normative-symbolic, not yet transformational. The state has banned its acts, but has not adequately guaranteed the recovery of victims and the breaking of the cycle of exploitation. This condition shows the urgency of reforming criminal law policies that not only place illegal organ transplantation as a serious crime, but also integrate a comprehensive approach to victim protection through strengthening victim identification, restitution, rehabilitation, and cross-sectoral and cross-country cooperation.